TPLATE complex-dependent endocytosis attenuates CLAVATA1 signaling for shoot apical meristem maintenance - Wang, Jie; Jiang, Qihang; Pleskot, Roman; Grones, Peter; Bahafid, Elmehdi; Denay, Grégoire; Galván-Ampudia, Carlos; Xu, Xiangyu; Vandorpe, Michael; Mylle, Evelien; De Smet, Ive; Vernoux, Teva; et al. (EMBO reports, 2023)
Endocytosis regulates the turnover of cell surface localized receptors, which are crucial for plants to rapidly respond to stimuli. The evolutionary ancient TPLATE complex (TPC) plays an essential role in endocytosis in Arabidopsis plants. Knockout or knockdown of single TPC subunits causes male sterility and seedling lethality phenotypes, complicating analysis of the roles of TPC during plant development. Partially functional alleles of TPC subunits however only cause mild developmental deviations. Here, we took advantage of the partially functional TPLATE allele, WDXM2, to investigate a role for TPC-dependent endocytosis in receptor-mediated signaling. We discovered that reduced TPC-dependent endocytosis confers a hypersensitivity to very low doses of CLAVATA3 peptide signaling. This hypersensitivity correlated with the abundance of the CLAVATA3 receptor protein kinase CLAVATA1 at the plasma membrane. Genetic and biochemical analysis as well as live-cell imaging revealed that TPC-dependent regulation of CLAVATA3-dependent internalization of CLAVATA1 from the plasma membrane is required for shoot stem cell homeostasis. Our findings provide evidence that TPC-mediated endocytosis and degradation of CLAVATA1 is a mechanism to dampen CLAVATA3-mediated signaling during plant development.
Keywords: Plants; signální transdukce; Signal Transduction; proteiny huseníčku; clathrin-mediated endocytosis; Arabidopsis Proteins; Endocytosis; regulace genové exprese u rostlin; CLAVATA3-CLAVATA1 signaling; Gene Expression Regulation, Plant; receptory buněčného povrchu; endocytóza; Arabidopsis; Receptors, Cell Surface; meristém; TPLATE complex; shoot apical meristem maintenance; Meristem; rostliny